Epistemologi Ibnu Rusyd dan Relevansinya Terhadap Kurikulum Pendidikan Islam Kontemporer - Latifah Latifah; Normuslim Normuslim (Madrasah: Jurnal Pendidikan Madrasah, 2026)
This study analyzes the relevance of Ibn Rushd’s epistemology as a conceptual foundation for reconstructing the contemporary Islamic education curriculum. Using a library research method with a qualitative descriptive-analytical approach, it examines Ibn Rushd’s primary works Fashl al-Maqal, Tahafut al-Tahafut, and Bidayat al-Mujtahid as well as modern literature on the integration of knowledge and educational reform. The findings reveal that Ibn Rushd places reason (‘aql) and revelation (wahy) as complementary sources of truth. Through three epistemic approaches burhani (demonstrative), jadali (dialectical), and khaṭabi (rhetorical) he constructs a rational and hierarchical structure of knowledge. This paradigm rejects the dichotomy between religion and science while promoting critical reasoning and rational interpretation (ta’wil). In the context of modern Islamic education, Ibn Rushd’s thought is relevant for developing an integrative curriculum that unites religious and scientific knowledge through research-based learning, critical discussion, and epistemological training for teachers. Although challenges remain such as textualist dominance and limited access to classical literature curriculum reform, digitalization of classical works, and pedagogical renewal are strategic steps forward. Thus, Ibn Rushd’s epistemology serves as an essential foundation for building a rational, holistic, and contextual Islamic education curriculum without abandoning its normative values.